Results of a Phase II Study of Short-Course Accelerated Radiation Therapy (SHARON) for Multiple Brain Metastases. (August 2015) - Caravatta, Luciana; Deodato, Francesco; Ferro, Marica; Macchia, Gabriella; Massaccesi, Mariangela; Cilla, Savino; Tambaro, Rosa; Mignogna, Samantha; Padula, Gilbert D. A.; Musacchio, Michela; Flocco, Mariano; Cantore, Giampaolo; et al.
Abstract : Objectives: To assess the effectiveness of a SHort-course Accelerated RadiatiON therapy (SHARON) in the treatment of patients with multiple brain metastases. Materials and Methods: A phase II clinical trial was designed. Eligibility criteria included patients with at least 3 brain metastases or metastatic disease in >3 organ systems, and Eastern Cooperative Oncology Group performance status of ⩽3. Fifty patients were treated with whole brain radiotherapy at 18 Gy (4.5 Gy per fraction) in 2 days with a twice daily fractionation. The primary endpoint was the assessment of efficacy in terms of overall survival. Results: Characteristics of the 50 enrolled patients were: male/female: 24/26; median age: 65 years (range, 45 to 80 y). Eastern Cooperative Oncology Group performance status was <3 in 42 patients (84%). Nineteen patients (38%) were considered to have recursive partitioning analysis class 3 disease. Grade 1-2 acute neurological (46%) and skin (24%) toxicities were recorded. Three patients (6%) experienced neurological grade 3 acute toxicity. With a median follow-up time of 6 months (range, 1 to 18 mo) 2 skin grade 1 late toxicities has been observed. Seventeen of 27 symptomatic patients showed an improvement or resolution of baseline symptoms (overall palliative response rate: 63.0%; 95% confidence interval, 36.6%-82.4%).Two-month overall survival was 86% (median survival time=7 mo). Conclusions: Short-course accelerated whole brain radiotherapy of 18 Gy in twice daily fractions for 2 consecutive days is tolerated and effective in terms of symptom relief and median survival time. These results justify a phase III comparison against the standard-of-care in this patient population (30 Gy in 10 fractions).